Case report: The use of medical yoga for adolescent mental health. (April 2019) - Stephens, Ina
Abstract: Mental health issues are epidemic among youth in the United States today. Recent studies suggest that up to 50% of all teenagers have complaints related to stress, anxiety, and/or depression. This problem is accompanied by an unprecedented rise in the rates of child and teen suicide in the United States. In response to this epidemic, the American Academy of Pediatrics is recommending universal depression screening for all teens. Medications are available to ameliorate mental health disorders, and many can be safely used in the primary care setting. However, many of these medications have unwanted side effects or may not be familiar to the primary care physician. For these reasons and others, primary care physicians require additional approaches to respond to the challenges imposed by a growing number of patients requiring mental health support. Medical Yoga Therapy, prescribed by a physician with special yoga therapy training, offers a safe and effective way to serve the patient with physical or mental challenges disabilities. Medical Yoga therapy is an individualized and personal approach to the patient, and it may be integrated with any current therapy or medical regimen. Here, evidence for medical yoga is reviewed in the context of an adolescent patient with a common disorder. Yoga practices, with particular focus on mindfulness, offer a safe and effective intervention for a growing number of pediatric patients.